The Position Losing of Animal Husbandry in Agriculture - Nemessályi, Zsolt (Applied Studies in Agribusiness and Commerce, 2009)
The author in the presentation deals with the fact that what caused the decline of animal husbandry in contrast with plant production; how this unfavourable ratio of 60:40 could evolve when comparing plant production and animal husbandry What the reason is for the decreasing animal stock; and how the effect of changes in the elements of the economic efficiency such as yields, prices, subsidies, production value, inputs, costs, profits can be evaluated in case of more important animal husbandry enterprises highlighting several significant animal products.